Development of Social Science Teaching Modules in the Implementation of the Independent Curriculum at the Junior High School Level in Pekanbaru - Walni Fitri; Mahdum Mahdum; Henny Indrawati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The Indonesian Education and Culture Ministry's autonomous curriculum teaching modules were used to construct social studies teaching modules. Because the Ministry only provides general examples, richer modules tailored to schools and students were developed. Class VII modules were produced using ADDIE model RD. The first step was a needs and empirical study of SMP Pekanbaru social studies teaching modules involving student and teacher observations and interviews. The modules were designed and developed using Canva Education and e-modules. Six experts validated the module's practicality. Other Pekanbaru junior high social studies teachers discussed the module. Qualitative analysis of validation questionnaire data. After the material was approved, SMP Pekanbaru social studies educators adopted it. Twenty students were given a learning motivation questionnaire to test the curriculum. Teachers who implemented the module received practical surveys and module usefulness at the end of the activity. Motivational and practical surveys were quantitatively analysed, and the Wilcoxon difference test was used to compare learning motivation before and after the module. The module enhanced student learning motivation; 100% of students were high and sufficient after using it, up from 90% before. The teachers also liked the module and thought it was practical and valuable.